Is pancreaticodoudenectomy with vascular resection a safe procedure in developing country? Early outcomes and review of national literature. (September 2015) - Dar, Faisal Saud; Bhatti, Abu Bakar Hafeez; Dogar, Abdul Wahab; Zia, Haseeb; Ulhaq, Ihsan; Rana, Atif; Khan, Nasir Ayub; Liaqat, Amna; Salih, Muhammad; Shah, Najmul Hassan
Abstract: Introduction: Safety of extended lymphadenectomy (EL) ± vascular resection in patients undergoing pancreaticoduodenectomy (PD) in resource limited settings is not well established. The objective of this study was to report outcomes of PD resection with EL ± vascular resection from Pakistan and review national literature. Methods: Data of patients who underwent PD between 2011 and 2014 was reviewed. A total of 66 patients were included in the study. Primary outcome was 90 day morbidity and mortality. Secondary objective was 2 year overall survival. Results: Median age was 57 (32–82) years. Majority patients had locally advanced (pT3/T4) tumors and nodal involvement i.e. 44 (71%) and 42 (67.8%). Mean number of excised lymph nodes and positive lymph nodes was 28.2 ± 12.8 (range 3–62) and 4.8 ± 6.9 (range 0–27) respectively. There were 13 vascular resections including 3 arterial resections. Overall 90 day morbidity was 31.8% and mortality was 3%. No difference in complication rate was observed in patients who did and did not undergo vascular resection i.e. 18% versus 34.5% (P = 0.1). Similarly, median survival was 11 (3–24) months and 11 (1–36) months and not significantly different (P = 0.5). Conclusion: In developing countries, extended lymphadenectomy with vascular resection can be safely performed with pancreaticoduodenectomy in specialized hepatobiliary units. Highlights: Impact of extended lymphadenectomy (EL) in pancreatic cancer remains unknown. Role of vascular resections is also ill defined. Should extended procedures be performed in developing countries? Current study shows low complication rate associated with EL or vascular resections.